Status zawodowy nauczyciela - Tyl, Anna (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
The basis of theoretical investigation is the definition of „professional status” meaning professional position that results from being employed at a certain post. The structure of the text is an outcome of dichotomic interpretation of the definition. From one hand, professional status means the position the people employed at the post enjoy depending on the degree of recognition of their function and competence. The text tackles the issue of the hierarchy of professions according to the criterion of prestige and indicates the place of teacher’s profession in such rank lists. From the other hand, professional status determines the range of rights and responsibilities of an employee. What needs to be discussed is the pragmatics of a Polish teacher’s profession and, as its result, the categories of teacher’s professional status (status of career civil servant and a status of public status employee) taking into consideration a rank of professional promotion of a teacher.